1981
DOI: 10.1088/0029-5515/21/3/002
|View full text |Cite
|
Sign up to set email alerts
|

Electron cyclotron/upper hybrid resonant pre-ionization in the ISX-B tokamak

Abstract: Pre-ionization experiments have been performed on a tokamak by injecting about 80 kW of microwave power at 35 GHz for up to 15 ms. Microwave absorption occurs at the electron cyclotron and upper hybrid resonance frequencies as predicted by theory. Pre-ionization causes substantial (40%) reductions in loop voltage during the initial phase of the tokamak shot. Flux (volt-second) savings with pre-ionization are about 30% in the first 2 ms or about 2% of the total flux expenditure in a tokamak shot. The plasma cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…By injection of microwaves at the ECR frequency, breakdown easily takes place at the ECR layer, after which the discharge is maintained by the deposition of the microwave power at the ECR layer and/or the upper hybrid resonance (UHR) layer [1,2]. This is a standard method of pre-ionization and heating to assist the start-up of plasma current in tokamaks [3]. This technique is intended to be used for the International Thermonuclear Experimental Reactor tokamak [4].…”
Section: Introductionmentioning
confidence: 99%
“…By injection of microwaves at the ECR frequency, breakdown easily takes place at the ECR layer, after which the discharge is maintained by the deposition of the microwave power at the ECR layer and/or the upper hybrid resonance (UHR) layer [1,2]. This is a standard method of pre-ionization and heating to assist the start-up of plasma current in tokamaks [3]. This technique is intended to be used for the International Thermonuclear Experimental Reactor tokamak [4].…”
Section: Introductionmentioning
confidence: 99%
“…Electron cyclotron resonance (ECR) assisted pre-ionization is a common technique used in tokamaks [1][2][3][4][5][6][7][8][9][10][11][12], stellerators [13,14] and other plasma devices such as tokapole [15] for start-up and to assist plasma formation in the initial stage of the discharge. In ohmic discharge, high loop voltage is required to initiate the discharge when plasma density, temperature and conductivity are low and the line radiation from impurities are the dominating losses.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies by Anisimov et al [27] indicated the feasibility of UHR absorption by a plasma in a purely toroidal magnetic field, but only for short pulse lengths (<1 as). Recently, longer pulse (-15 ms) preionization experiments on the much larger ISX-B tokamak [28,35] have also confirmed UHR absorption and heating using time-resolved density measurements, temperature diagnostics and high-speed photography to examine the plasma characteristics during preheating. To provide the physics basis for the UHR preheating process examined in this study, this section briefly reviews the criterion for wave-plasma interactions at the UHR.…”
Section: Physics Discussion Of Wave-plasma Interactionsmentioning
confidence: 99%